Exploring the Impact of Flexible Work Arrangements on Turnover Intention: The Mediating Role of Job Satisfaction and the Moderating Effect of Perceived Supervisory Support - George, Joanna Benjamin; Poluru, Nitin Vihari (STIE Malangkucecwara, 2024)
In today's employment landscape, the value of flexibility cannot be overstated, with an increasing number of employees seeking to balance their professional duties with their personal lives. This quest for the right balance has been strengthened by workplace flexibility, allowing individuals to tailor their workloads and have more autonomy over their working conditions. This research focuses on the impact of Flexible Work Arrangements (FWAs)—namely, working from home and flextime—on Turnover Intention (TI) within the power and utilities sector of the United Arab Emirates (UAE). We further investigate how Job Satisfaction (JS) mediates this relationship, and the extent to which Perceived Supervisory Support (PSS) moderates it. The study utilized a convenience sampling method to survey employees from a leading global energy company with a significant presence in Abu Dhabi and Dubai, boasting over 500 staff members. Of the 550 employees approached, 250 responded, yielding a 45% response rate. The research employed SPSS V.28 for demographic analysis, descriptive statistics, correlation analysis, and measurement of the reliability and validity of the study constructs. Also, mediation and moderation analysis were performed using Hayes Process Macro to validate our conceptual framework, providing robust statistical analysis. This research focuses on how PSS moderates the relationship between FWAs and Job Satisfaction, a relatively underexplored area. The findings include, FWA has positive impact on Job Satisfaction and negative impact on turnover intention. The indirect effect of Job Satisfaction and Perceived Supervisor Support is found out to be insignificant. The implications of this study guides organizations in tailoring their policies, and practices to mitigate turnover intentions.